To simplify the expression 5a - 8c + v + 3c - 9a + 6b, we can combine like terms:
Combine the "a" terms:
5a - 9a = -4a
Combine the "c" terms:
-8c + 3c = -5c
So far, we have:
-4a - 5c + v + 6b
The expression is now simplified.
Simplify 5a-8c+v+3c-9a+6b
11 answers
simplify -3/4r+3-5/6r
To simplify the expression -3/4r + 3 - 5/6r, we can combine like terms:
Combine the "r" terms:
-3/4r - 5/6r = -18/24r - 20/24r = -38/24r = -19/12r
So far, we have:
-19/12r + 3
The expression is now simplified.
Combine the "r" terms:
-3/4r - 5/6r = -18/24r - 20/24r = -38/24r = -19/12r
So far, we have:
-19/12r + 3
The expression is now simplified.
Expand 8(3p+2)
To expand the expression 8(3p + 2), we distribute the 8 to each term inside the parentheses:
8(3p + 2) = 8 * 3p + 8 * 2
This simplifies to:
24p + 16
Therefore, the expanded form of the expression 8(3p + 2) is 24p + 16.
8(3p + 2) = 8 * 3p + 8 * 2
This simplifies to:
24p + 16
Therefore, the expanded form of the expression 8(3p + 2) is 24p + 16.
Expand -4(6a-5)
To expand the expression -4(6a - 5), we distribute the -4 to each term inside the parentheses:
-4(6a - 5) = -4 * 6a + (-4) * (-5)
This simplifies to:
-24a + 20
Therefore, the expanded form of the expression -4(6a - 5) is -24a + 20.
-4(6a - 5) = -4 * 6a + (-4) * (-5)
This simplifies to:
-24a + 20
Therefore, the expanded form of the expression -4(6a - 5) is -24a + 20.
Expand 7/4(8h+3)
To expand the expression 7/4(8h + 3), we distribute the 7/4 to each term inside the parentheses:
7/4(8h + 3) = (7/4) * 8h + (7/4) * 3
Using the distributive property and simplifying:
(7/4) * 8h + (7/4) * 3 = 56/4h + 21/4
We can further simplify by dividing the numerator of each fraction by the denominator:
56/4h + 21/4 = 14h + 21/4
Therefore, the expanded form of the expression 7/4(8h + 3) is 14h + 21/4.
7/4(8h + 3) = (7/4) * 8h + (7/4) * 3
Using the distributive property and simplifying:
(7/4) * 8h + (7/4) * 3 = 56/4h + 21/4
We can further simplify by dividing the numerator of each fraction by the denominator:
56/4h + 21/4 = 14h + 21/4
Therefore, the expanded form of the expression 7/4(8h + 3) is 14h + 21/4.
simplified?
The simplified form of 7/4(8h + 3) is 14h + 21/4.